Isolated adenocarcinoma of the nipple. (27th July 2011) - Ahmed, M; Basit, A
Abstract : A 47-year-old female presented with a 1-year history of 'eczematous change' to the right nipple. Bilateral mammography and ultrasound were entirely normal. Free hand biopsy demonstrated invasive adenocarcinoma of the nipple. The patient underwent a right-sided central segmentectomy and sentinel node biopsy. Histology demonstrated that the nipple was almost completely replaced by an invasive ductal carcinoma with a maximum diameter of 13 mm. Invasion of the underlying breast tissue was to a depth of 3 mm. A single sentinel lymph node demonstrated metastatic carcinoma. Her oestrogen receptor status was positive while HER-2 status was negative. The patient subsequently underwent right-sided axillary node clearance to level three nodes. All 17 nodes in the specimen were found to be within normal limits. She is scheduled to undergo radiotherapy, chemotherapy and hormonal treatment.